Effect of Muladhara moxibustion on perineal injury during childbirth and physical rehabilitation of parturients (新型底轮灸治疗对产后会阴伤口及体质康复的影响) - DENG Yanling (邓燕玲); HUANG Yuchang (黄裕嫦); PENG Yingfeng (彭荥枫); LIN Jin (林金); XIONG Mei (熊梅); YANG Li (杨丽) (中西医结合护理)
Objective To investigate the effect of Muladhara moxibustion on perineal injury during childbrith and physical rehabilitation of parturients. Methods According to the random number table method, 74 women with postpartum perineal injury were randomly divided into observation group and control group, with 37 participants in each group. The control group received the routine care plan, while the observation group added the Muladhara moxibustion treatment on the basis of the routine care plan for 3 days. The wound pain, swelling, perineal wound healing and Traditional Chinese Medicine symptom scores of the two groups were compared. Results After intervention, the wound pain score in the observation group was significantly lower than that in the control group (P＜0. 05). The degree of swelling decreased more significantly in the observation group than that in the control group (P＜0. 05), and there was no significant difference in wound healing between two groups. After treatment, the scores of Traditional Chinese Medicine symptoms, such as fatigue, spontaneous sweating, lumbago, complexion and other clinical symptoms in the observation group were significantly lower than those of the control group(P＜0. 05). Conclusion Muladhara moxibustion treatment can effectively reduce pain, swelling and other accompanying symptoms, to a certain extent improve the postpartum Qi and blood weakness, with high treatment safety and effectiveness. (目的 探讨新型底轮灸促进产妇产后会阴伤口愈合和体质康复的效果。方法 根据随机数表法, 将74名产后会阴损伤的产妇随机分为观察组和对照组, 各37例。对照组接受常规护理方案, 观察组在常规护理方案基础上增加底轮灸治疗, 持续3 d。比较两组伤口疼痛、肿胀情况、会阴伤口愈合情况以及两组产妇中医症候得分。结果 干预后观察组伤口疼痛分数低于对照组, 差异有统计学意义(P＜0. 01); 观察组肿胀程度减轻较对照组更为显著, 差异有统计学意义(P＜0. 01); 伤口愈合情况两组差异无统计学意义(P＞0. 05)。治疗后两组中医症候得分对比, 观察组产妇倦怠乏力、自汗、腰酸、面色无华等临床症候评分明显较低(P＜0. 05)。结论 新型底轮灸治疗可有效减轻疼痛、肿胀等伴随症状, 一定程度改善产妇产后气血虚弱体质, 具有较高的治疗安全性和有效性。)